The most precious gift : a story of the Nativity - Crisp, Marty; Cooper, Floyd (New York : Philomel Books, 2006)
While traveling to Bethlehem with his beloved dog, a young servant to one of the Magi worries about finding a gift to give the baby Jesus.
Keywords: Jesus Christ -- Nativity -- Juvenile fiction; Jesus Christ -- Nativity -- Fiction; Dogs -- Fiction; Household employees -- Fiction